Ethics Creep: Governing Social Science Research in the Name of Ethics - Haggerty, Kevin D. (Qualitative sociology, 2004)
This article presents an analysis of the Canadian ethics review process by a member of a Research Ethics Board. The author suggests that the new formal system for regulating the ethical conduct of scholarly research is experiencing a form of "ethics creep." This is characterized by a dual process whereby the regulatory system is expanding outward to incorporate a host of new activities & institutions, while at the same time intensifying the regulation of activities deemed to fall within its ambit. These tendencies are demonstrated through an analysis of (1) the scope of research ethics protocols, (2) the concept of "harm" employed by these boards, (3) the use of informed consent provisions, & (4) the presumption that research participants will remain anonymous. To accentuate the nature of this ethics creep, comparisons are made between the ways in which identical knowledge-generation activities are governed within journalism & the academy. The conclusion suggests that one effect of the increasingly formalized research ethics structure is to rupture the relationship between following the rules & acting ethically. Some of the reasons for this "creep" are highlighted along with the risks that it poses for scholarship. 33 References. Adapted from the source document.